2013
DOI: 10.1159/000351158
|View full text |Cite
|
Sign up to set email alerts
|

A Common <b><i>APOE</i></b> Polymorphism Is an Independent Risk Factor for Reduced Glomerular Filtration Rate in the Spanish RENASTUR Cohort

Abstract: Objective:APOE gene variants may contribute to the risk of chronic kidney disease. Our aim was to determine whether the common APOE-ε2/ε3/ε4 polymorphism is associated with a reduced estimated glomerular filtration rate (eGFR) in the RENASTUR population, a cohort of elderly individuals from the region Asturias (northern Spain). Methods: A total of 743 Spanish Caucasians aged 55-85 years were genotyped for the APOE-ε2/ε3/ε4 polymorphism. Individuals with a previous diagnosis of renal disease were not eligible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“… 14 , 17) However, other researchers have reported no association between APOE alleles and HDL cholesterol levels. 19 , 20) Many investigators have demonstrated that participants with the APOE E3 allele have the lowest triglyceride levels, 14 , 18 , 20) similar to our results. However, another study reported that female subjects with the APOE E2 allele have the lowest triglyceride levels.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“… 14 , 17) However, other researchers have reported no association between APOE alleles and HDL cholesterol levels. 19 , 20) Many investigators have demonstrated that participants with the APOE E3 allele have the lowest triglyceride levels, 14 , 18 , 20) similar to our results. However, another study reported that female subjects with the APOE E2 allele have the lowest triglyceride levels.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, studies in general populations have not demonstrated consistent results. Some studies have reported a significant association between the APOE E2 allele and CKD, 19 , 20) whereas others indicate that the APOE E4 allele is associated with a decreased risk of CKD. 24 , 25) Yet others have reported no association between APOE polymorphisms and the prevalence of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…alzgene.org/). Besides AD and CVD, genetic studies have also connected APOE and its ε2/ε3/ε4 alleles to multiple physiological conditions and disorders, including aging (18,19), diabetes (20), dysbetalipoproteinemia (21), frontotemporal dementia (22), fragile X-associated ataxia (23), glomerulopathy (24), Lewy body dementia (25), metabolic syndrome (26), retinal-related disorders (27) disease (28), posttraumatic stress disorder (29), primary progressive aphasia (30), schizophrenia (31), stroke (32), traumatic brain injury (33), and vascular dementia (34).…”
Section: Introductionmentioning
confidence: 99%
“…They were recruited through the Primary Healthcare Center of the city of Oviedo to evaluate renal function in healthy elderly people, as reported [24]. Individuals with a history of renal disease or who had suffered episodes of cardiovascular disease were not eligible for the study.…”
Section: Methodsmentioning
confidence: 99%